MultiPathP2P: a simple multipath ant routing system for P2P networks. (2018) - Riahla, Mohamed Amine; Tamine, Karim
This paper presents MultiPathP2P that is a new routing protocol dedicated to P2P system. MultiPathP2P relies on the social networks concepts where nodes are identified through their virtual addresses. The proposed protocol will decrease the routing overhead within the network. The main idea consists of using mobile agents in order to find optimal routes towards the destination nodes. These agents are generated by each network node. Whenever a network node plans to request a resource in the network, it set a local resource request rather than broadcasting it. Then, this request will be shared among the others nodes using the agents which are moving within the network. We also present a data routing protocol based on ant's general behaviour in order to increase the performance of MultiPathP2P. The simulation results show that our new algorithm provide a significant improvement in terms of various performance metrics compared to other protocols.